THE RELATIONSHIP BETWEEN SOCIO-CULTURAL ASPECTS AND THE PHYSICAL SETTING OF MUNCAR COASTAL SETTLEMENT - Filomina Dwi Cayarini; Agung Murti Nugroho; Damayanti Asikin (Department of Architecture Universitas Muhammadiyah Jakarta, 2023)
Muncar has been developed into a core Minneapolitan area since 2012. The development of the Minneapolitan area can affect the socio-cultural aspects of the fishing community which then affects the physical setting of the coastal settlement, which is actually part of the ekistics elements of the settlement. This research aims to examine the relationship of the socio-cultural aspects of the Muncar fishing community especially in Sampangan Hamlet to the condition of its physical setting which is associated with ekistics elements in the form of networks and buildings. The method used in the research is descriptive-qualitative with spatial analysis and community field studies related to the influence of local socio-culture on the physical setting. Based on the research results, it is known that socio-cultural aspects affect settlement patterns, building orientation directions, landform changes, space utilization, gender-based activity spaces and the formation of cultural spaces in the reclamation area.